Measurements of LSTID and LSTAD using TEC and GOCE data - Valladares, C. E.; Chen, Y.-J.; Bukowski, A.; Adhya, P.; Anderson, P. C.; Dey, S.; Hairston, M. (Frontiers in Astronomy and Space Sciences, 2025)
This paper presents measurements gathered with the Gravity Field and Ocean Circulation Explorer (GOCE) satellite, TEC values collected in the American sector, and Poynting Flux (PF) derived using the electric and magnetic fields from the Defense Meteorological Satellite Program (DMSP) satellites aiming to elucidate the mechanisms controlling the initiation of large-scale traveling atmospheric disturbances (LSTAD) and the transit and asymmetry of concurrent large-scale traveling ionospheric disturbances (LSTID). LSTADs and LSTIDs measured during twelve intense magnetic storms that occurred between 2011 and 2013 are thoroughly analyzed. The LSTAD/LSTID appearance and characteristics are correlated against the PF values and the auroral oval’s location, measured by the DMSP satellites. GOCE data and TEC values are used to assess the perturbation of the vertical wind and TEC (∂TEC), inter-hemispheric asymmetry of the appearance of LSTIDs, and the role of the different phases of storms and the structures within interplanetary coronal mass ejections (ICME). Emphasis is devoted to examining LSTADs and LSTIDs during the storms of 5–6 August 2011, 15 July 2012, and 17 March 2013, the supporting material reports on the dynamics of LSTADs and LSTIDs for nine additional storms. During most storms, LSTIDs initiate from both auroral ovals and propagate toward the opposite hemisphere. However, on 5 August 2011 and 15 July 2012, LSTIDs moved only from one hemisphere toward the opposite. Close inspection of the TEC perturbation associated with these events indicates that LSTIDS onsets at opposite hemispheres occur at different times and intensities. This timing delay is produced by the difference in the amount of PF deposited in each hemisphere. It is also indicated that LSTAD’s initiation occurs when the PF is above 1 mW/m2 and when the lower latitude edge of the auroral oval moves equatorward at 65°. In addition, LSTIDs are observed during the passage of ICME sheath (in 6 storms), magnetic clouds (11), and Sunward Loops (1), although they occur when the IMF Bz is predominantly directed southward. The observations suggest that the interhemispheric asymmetries in the LSTIDs initiation, extension, and amplitude occur when the ICME sheath passes, containing rapidly varying IMF Bz sign fluctuations. TEC perturbations associated with the LSTID can be up to 4% of the background TEC value, and the LSTAD neutral density variability measured by GOCE can be up to 8%. LSTIDs are observed during all phases of magnetic storms.